Environmental Protection and Management of the National Capital Development in the perspective of Sustainable Development Goals - SAPUTRA, Rahmat; WIDIANSYAH, Apriyanti (Protection: Journal Of Land And Environmental Law, 2022)
The purpose of this study is to discuss how the form of environmental protection and management by the government is related to the development of the State Capital (IKN) from the perspective of sustainable development goals (SDGs) and how to apply the concept of forest city in the development plan of the State Capital (IKN). Empirical juridical research methods, through search and study of secondary data, in the form of legislation, academic texts, policy recommendations, and scientific works of experts in the field of National Capital Development (IKN). Secondary data was obtained through library research (Library Research) sourced from printed and electronic library materials. Normative research (doctrinal) is needed to understand the current legal norms (Law in the Book), through a statutory approach (Statute Approach) and a conceptual approach (Conceptual Approach). The results of the study that the forms of environmental protection and management including prevention, prevention of damage and pollution as well as restoration of environmental quality have demanded the development of various policies and programs as well as activities that are supported by other environmental management support systems. Sustainable development involving current and future generations require joint efforts to achieve the goals of IKN development, by balancing three important aspects, namely economic, social, and environmental protection. The application of the Forest City Concept in IKN development in the form of stabilizing forest areas and resolving various land conflicts within forest areas that need to be carried out before building IKN.